Partisipasi Masyarakat dalam Penyelenggaraan Festival Palang Pintu sebagai Atraksi Wisata Budaya di Kawasan Kemang Jakarta Selatan - Indri Dwi Hartono; Riza Firmansyah (Fakultas Pariwisata Universitas Pancasila, 2017)
Palang Pintu Festival is an annual program organized by Forkabi (Betawi Children's Communication Forum) DPRT Bangka Kemang and Betawi Cultural Center namely Padepokan Manggar Kelape featuring Betawi culture and performing arts and community participation. The purpose of the festival is to preserve and introduce Betawi culture in Kemang area. This study discusses the elements of cultural tourism and the form of community participation in the Palang Pintu Festival. Data collection methods used were observations, surveys using questionnaires, interviews, and documentation then analyzed and presented in quanititative manner and supported by qualitative data, where the results will be presented in the percentage number. Technique of data analysis used in this research is with validity test, reliability test and also use rank spearman analysis method. The result of this research shows that the characteristic of society is seen from the age type dominated by the age of 15-25 years as much as 39 % and the sexes, both men and women are the same size because this research uses roscoe theory in determining the number of respondents, if the sample is divided into 2 then Per sub sample to 30 respondents respectively. The level of community participation in the Palang Pintu Festival is at a moderate level, this is because the community participating in the Kemang area is more interested if the activities are rewarded. For a community characteristic relationship with participation does not have a strong relationship or it can be said has nothing to do in participation with the characteristics of society in any category. Because of all the people who participated in the Palang Pintu Festival plays an important role in preserving and introducing Betawi Culture to the wider community.